Clogging in subsurface wastewater infiltration beds: genesis, influencing factors, identification methods and remediation strategies - Ying-hua Li (IWA Publishing, 2021)
Subsurface wastewater infiltration (SWI) is an environmentally friendly technology for the advanced treatment of domestic sewage. Clogging (including physical, chemical and biological clogging) of the porous medium not only directly reduces the hydraulic load (treatment efficiency), but also reduces the service life. Although clogging has become one of the key issues discussed in several reports, there are still several gaps in understanding, especially in its occurrence process and identification. SWI clogging causes, development process and solutions are different from those of constructed wetlands. This article quotes some reports on constructed wetlands to provide technical ideas and reference for revealing SWI clogging problems. Based on the analysis of the clogging genesis, this review gathers the main factors that affect the degree of clogging, and new methods for the identification of clogging conditions. Some preventive and unclogging measures/strategies are presented. Finally, it is suggested that to effectively alleviate the clogging phenomenon and extend the service life, priority should be given to the comprehensive analysis of wastewater quality and solid constituents accumulated in the pores. Then, the effectiveness of in-situ strategies, such as alternating operation will be the main focuses of future research. HIGHLIGHTS Up to dated methods for the identification of clogging conditions were compared.; Main factors that affect the probability and degree of clogging were gathered.; Different preventive and unclogging measures/strategies were compared.; Priority unclogging measurements are proposed.;